Patch of sky - Yulo, Teresa Nicole L. (New York : Dial Books for Young Readers, 2022)
After learning pigs are unable to look up, Pia is on a mission to find a way for her and best pig pal, Patches, to share the beauty of the sky.
Keywords: Human-animal relationships -- Juvenile fiction